Extreme Copper Isotope Fractionation Driven by Redox Oscillation During Gleysols Weathering in Mun River Basin, Northeast Thailand. Issue 3 (3rd March 2023) - Zheng, Xiaodi; Han, Guilin; Zhang, Qian; Liang, Bin; Liu, Man; Yu, Changxun; Liu, Linan; Zhao, Ye; Song, Zhaoliang
Abstract: Copper (Cu) isotopes are utilized to track Cu geochemical cycling in weathered gleysols of tropical zones. A significant isotope fractionation of Cu in these soils is primarily redox‐controlled; however, it is rarely reported how the frequency of redox fluctuations affects the soil Cu isotope signature. This study investigated the variations of Cu content and isotope fractionation in two low‐humic gleysol profiles (S1 and S2) from a dry tropical savanna zone. Owing to redox oscillation during weathering, δ 65 Cu values in profile S2 showed a stronger positive correlation with the mafic index of alteration of reducing environment than S1, and isotopically light Cu is more retained in the Zone II of profile S2 than S1. As the frequency of redox fluctuation increased, the retained stable Cu(I) species and light Cu isotopes increased in the residual soils through re‐adsorption or re‐precipitation by iron oxyhydroxide (i.e., ferrihydrite). Importantly, an Mn‐enriched zone was formed after reduction events in profile S2, and found to be enriched in light Cu isotopes. The heavier Cu fraction might be lost by adsorption on Fe oxyhydroxides in the Mn‐rich zone, while the relatively light Cu might be retained through adsorption on Mn oxyhydroxides. Additionally, a significant Soil Organic Carbon (SOC) contribution to Cu was found due to the high δ 65 Cu‐SOC correlation ( R 2  = 0.80) in S1 (depth <1 m). Therefore, our study shows that the Cu isotope signature can respond to redox changes in the terrestrial ecosystem, and these Cu isotope signatures may have significant implications for assessing soil ecological vulnerability under future climate change scenarios. Plain Language Summary: The fractionation of copper (Cu) isotope is a process related to the redox fluctuation during soil Cu biogeochemical cycling. For Cu isotope composition in weathered gleysols of tropical zones, the increased rates of redox fluctuations are assumed to occur during gleysol evolution due to the seasonal exchange of groundwater and river water. However, the impact of the frequency of redox fluctuations on soil Cu isotope signatures is rarely documented. Here, we analyzed the variations of Cu content and isotope fractionation in two low‐humic gleysol profiles with different pedogenetic processes during weathering in the same basin (Mun River Basin), and found that the frequency of redox fluctuations could determine the magnitude of Cu isotope fractionation. We record an increased light Cu isotopes and identify the stable Cu(I) species retained in the residual soils with the increased frequency of redox fluctuation. Several processes contribute to Cu isotope fractionation at different soil horizons, but most isotope fractionation is related to the re‐adsorption or re‐precipitation by iron and manganese oxyhydroxide (i.e., ferrihydrite and pyrolusite), especially at the iron or manganese‐rich zone. Cu isotope fractionation is sensitive to increased redox fluctuations in the terrestrial ecosystem, and may have significant implications for assessing soil ecological vulnerability under future climate change scenarios. Key Points: Extremely light δ 65 Cu values (−1.20‰ to −1.16‰) were reported to date in the residual soils The Cu isotope fractionation was driven by redox fluctuations during gleysols weathering in Mun River Basin Cu isotope fractionation was sensitive to increased redox fluctuations in the terrestrial ecosystem